2014
DOI: 10.1016/j.jped.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

A randomized triple-masked controlled trial on the effects of synbiotics on inflammation markers in overweight children

Abstract: the present findings suggest the positive influence of synbiotic supplementation on inflammation factors, which are dependent to its effect on weight reduction in overweight and obese children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…The synergistic benefits have been documented for disease conditions such as obesity and diabetes. A study by Kelishadi et al evaluated the anti-inflammatory effects of synbiotics in the overweight pediatric population [21]. Their data suggested that therapy with synbiotics had an impact on inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…The synergistic benefits have been documented for disease conditions such as obesity and diabetes. A study by Kelishadi et al evaluated the anti-inflammatory effects of synbiotics in the overweight pediatric population [21]. Their data suggested that therapy with synbiotics had an impact on inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…According to these results, it can be proposed the favorable effects of probiotics in reducing inflammation in obese people 12 . In fact, studies have suggested some beneficial effects of probiotics in controlling excess weight in adults 13 ; experience, however, is limited in children.…”
Section: Sirsmentioning
confidence: 96%
“…In fact, studies have suggested some beneficial effects of probiotics in controlling excess weight in adults 13 ; experience, however, is limited in children. Kelishadi et al 12 supplemented synbiotics (combination of probiotic and prebiotic) in obese children and adolescents and concluded that supplementation reduced the inflammatory markers levels (IL-6, TNF-a), which are dependent to its effect on weight reduction in overweight and obese children.…”
Section: Sirsmentioning
confidence: 99%
“…Synbiotics are a mixture of pro- and prebiotics which, when ingested, are able to modulate gut microbiota and intestinal immunity ( 151 ). In a recent clinical trial, Kelishadi and associates ( 152 ) have administered overweight children with a synbiotic (Protexin-London, England) composed by a combination of viable Lactobacilli of human origin and fructo-oligosaccharides, as prebiotics. Treated subjects exhibited a significant reduction in weight as well as in TNF-α and IL-6 with an increase in adiponectin in comparison to the placebo group.…”
Section: Probioticsmentioning
confidence: 99%